Implementasi Good Corporate Governance (GCG) Dalam Pengelolaan Manajemen Risiko Di PT. Bank Sumut KCP Syariah Marelan Raya - M. Iqbal; Amzar Rafie; Astri Astri; Fauziah Amarani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to investigate in depth the implementation of Good Corporate Governance (GCG) in company risk management. By analyzing how GCG principles are implemented, this research will identify their impact on organizational risk management. The focus involves concrete evaluation of policies, organizational structures and monitoring mechanisms related to GCG. This research uses a qualitative method which is a natural research design, meaning that the researcher does not try to manipulate the research setting, but rather carries out a study of a phenomenon. The research results are expected to provide in-depth insight into how the implementation of GCG can improve the efficiency of risk management and overall corporate welfare.